Medição da impedância e da resistência de aterramento utilizando ondas impulsivas e cabos de pequeno comprimento nos circuitos de tensão e de corrente - Alexander Barros Lima (2015)
This PhD thesis presents a technique used in grounding impedance and resistance measurementswhere the current circuit consisting of a typically long single wire is replaced by an Artificial InfiniteLine. Due to the constructive characteristics, this element is similar to transmission line withnegligible losses and low speed propagation. The mainattractiveness of this element is that itslength is small compared with those circuits that use single wire. The effectiveness of this elementwas verified by measurements under real field conditions. Furthermore, grounding impedance is alsodetermined with unconventional techniques, one in which the electrode of the voltage circuit is notpositioned in a place where there is no potential rise on the ground and in the another one thecurrent circuit is not grounded at far end (open line). In the first one, the technique makes it possibleto determine de impedance with a voltage circuit shorter than conventional circuit. In the secondone, do not ground the far end of the current circuit is particularly interesting when earth inmeasurement site is not available. The results of measurements performed in the field to determinethe grounding resistances with the same arrangement used to determine the impedance are alsoshown. A comparison of results was made with values obtained with a resistance tester becomingclear a good agreement of results and the effectiveness of the technique.